2004
DOI: 10.1194/jlr.m400087-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an n-3-deficient diet on brain, retina, and liver fatty acyl composition in artificially reared rats

Abstract: Rat pups born to dams fed a diet with 3.1% of total fatty acids as ␣ -linolenic acid (LNA) were fed, using an artificial rearing system, either an n-3-deficient (n-3-Def) or an n-3-adequate (n-3-Adq) diet. Both diets contained 17.1% linoleic acid, but the n-3-Adq diet also contained 3.1% LNA. The percentage of brain docosahexaenoic acid (DHA) continuously decreased (71%) with time over the 29 days of the experiment, with concomitant increases in docosapentaenoic acid (DPAn-6). In the retina, the percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…After 250 mg of methyl docosatrienoate (22:3n-3) was added as an internal standard (19), the fatty acids esterified to phospholipids in ?100 mg (wet weight) of tissue were transmethylated, and the fatty aldehydes were converted to dimethylacetals (20). Fatty acids and aldehydes were identified by matching sample retention times with those of standards (Agilent Technology, Wilmington, DE), with modifications to improve separation for DHA (21).…”
Section: Sds-page and Western Blotsmentioning
confidence: 99%
“…After 250 mg of methyl docosatrienoate (22:3n-3) was added as an internal standard (19), the fatty acids esterified to phospholipids in ?100 mg (wet weight) of tissue were transmethylated, and the fatty aldehydes were converted to dimethylacetals (20). Fatty acids and aldehydes were identified by matching sample retention times with those of standards (Agilent Technology, Wilmington, DE), with modifications to improve separation for DHA (21).…”
Section: Sds-page and Western Blotsmentioning
confidence: 99%
“…Severe depletion of brain DHA, approaching 80%, can be achieved by subjecting rats to n-3 PUFA deprivation for two or more consecutive generations (4, 9, 10), or by artificially rearing newborn pups on a formula free of n-3 PUFA (12). In addition, singlegenerational n-3 PUFA deprivation in rodents, starting after weaning at 21 days, reduces brain DHA by about 40% (11,13).…”
mentioning
confidence: 99%
“…Lipid content of milk reflects the lipid profile of the mother's diet 9,11 . We found that retinal lipid composition in the pups reflected the pups' (and the mother's) dietary intake of lipids.…”
mentioning
confidence: 99%